Minäkokemuksen merkitys liikuntamotivaatiotekijänä - Sarlin, Eeva-Liisa (1995)
The main aim of this study was to clarify, how significant self perception is for motivational orientation in Physical Education for the pupils of comprehensive school. The sectors of self perception are: self concept (perceived physical and school competence, social acceptance, appearance and self-worth) and the experiences from the programme of Physical Education. On the basis of Harter's competence motivation model, the model of daily Physical Education used in this study, was developed. Also the changes and stability of both self perception and motivational orientation in Physical Education during the comprehensive school was studied. The main group for the study were 188 sixth-grade pupils. The group of daily physical education (n=57) was formed by those who had attended the programme of daily Physical Education for at least two years. A mixed group (n= 65) was formed by those pupils, who had attended daily programme for a shorter period of time, and the control group (n=66) were those who had not attended the programme at all. Furthermore, the connections between pupils' evaluations on the first, second, third, and ninth grade and the evaluations of the pupils on the sixth grade, were studied. The study was implemented as a field experiment in schools in Kajaani and Kuhmo. Self concept and the motivational orientation of Physical Education were studied by means of device, which Harter had developed appropriate for each phase of age, and with methods applied to suit Physical Education. Pupils' experiences of Physical Education were also continuously monitored by method suitable for a pupil's age. The stability of self concept was studied by means of correlations and Simplex-model. The significance of perceived physical competence was studied also by means of confirmatory factorial model (Lisrel-model). The results show that the physical competence perceived during the lower stage of comprehensive school is an important factor in the process of self concept, and it functions as a mediating factor in the development of positive self-worth. The results are hypothesis-oriented, i.e. if a pupil considers Physical Education important and perceives that he/she is good at it, his/her self-worth is good. A correctly implemented programme of daily Physical Education does have significance in this process. Physical Education is more important sector of self concept for the pupils of the lower stage than it is for the pupils on the ninth grade. Person's concept of oneself is established during the lower stage of comprehensive school, and during the grades 6-9 there are very few changes. It also can be stated that self concept - especially perceived physical competence, the significance of Physical Education, and the experiences from Physical Education - does have an effect on motivational orientation in Physical Education. When daily physical education makes a child feel him/herself competent in Physical Education, consider it important and experience positive impressions of success, can the development of intrinsic motivation of Physical Education be enhanced. The model developed is to the purpose and active also when further research and practical applications are considered.